MINAT MUZAKKI MEMBAYAR ZAKAT MELALUI LEMBAGA (STUDI KASUS DI PROVINSI BENGKULU) - Asnaini Asnaini (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This research is about the interest of the community to pay zakat to the institution, what things can motivate the interest of muzakki in zakat to the institution, why they do not choose the zalcat institution as a means to distrib- ute the zakat, whereas Shari’ah and the rules of the law in Indonesia command the zakat managed by the institution. This study concludes that some people motives in tithe, there is a zakat to give compensation. Berzakat to keep the fraternity, avoid the conversation / slander of others, seek safe, or to remove the doubts / fears of zakatnya not to the rightful. These motives are highly individualized. This motif should not exist in zakah. Based on the motives described, to cultivate the interest of the community to pay zakat to BAZ institutions, can be done, among others: by providing a continuous understanding of the function, purpose, and nature of zakat ; providing a truly attractive BAZ institution, able to accommodate the needs of muzakki, able to provide muzakki and mustahik servants well; and able to build an emotional connection between institutions, muzakki and mustahik. In other words, the idol society agency BAZ is ready to guarantee and able to convince muzakki that his zakat will reach the right. Occasionally can include muzakki in distribution activities, and or provide reporting to muzakki to ensure that the given charity is really used for the need of prosperity mustahik.